Vandalism of public facilities in PPRT housing scheme / Francis Sta Gindi - Francis Sta Gindi (Faculty of Architecture, Planning and Surveying, 2013)
The purpose of this research is to identify and understand vandalism issues that occur in the selected case study site. This research was more to justify characteristics of the vandalism at public facilities on government building (Program Perancangan Rumah Termiskin). Questionnaire survey was conducted and specifically studies on case study. The research indicated that people perceived vandalism to occur because of the opportunities provided by the surroundings, user behavior, lack of security and enforcement, lack of maintenance and inspection, location and design of the facilities, and the materials used for such facilities. This research is very important because there is no other known research about of vandalism on PPRT building. More over than that this research helps planners, designers and local authority to understand and expand their knowledge of vandalism in PPRT.